Literature, instruction and education in the work of Antonio Candido The humanization of man - Machado, Márcia (Estudos Avançados, 2023)
As literature obtained primacy in Brazil’s cultural and intellectual life and occupies a prominent place in the work of Antonio Candido, in this article, based on his reflections, we strive to show some discussions on the contribution of literature to the formation and humanization of man. Because, on his journey, the critic also turned his attention to education, a less relevant aspect of his production when compared to others, such literary criticism. In this sense, it would not be an exaggeration to say that Candido provides important contributions, scholarly underpinnings, and theoretical tools to rethink how we have conceived the educational process and historically constructed the education and the university in Brazil.